Once daily antibiotic regimen in paediatric oncology. Issue 6 (June 1994) - Bouffet, E; Fuhrmann, C; Frappaz, D; Couillioud, D; Artiges, V; Charra, C; Bouhour, D; Brunat Mentigny, M
Abstract : The feasibility and efficacy of a once daily antibiotic regimen were assessed in children with malignant tumours. Over a 44 month period, 296 febrile episodes were treated with a regimen of once daily ceftriaxone-amikacin (and teicoplanin or vancomycin if the patient had a central line). The treatment was successful in 272 (92%) episodes without modification of the antibiotic regimen, and only one patient died of uncontrolled sepsis. A once daily antibiotic regimen is therefore feasible and worthwhile in the treatment of febrile episodes in children with cancer.